Native plant species with potential for the phytoremediation of high-andean soils contaminated by residues from mining activity (Bioagro, 2021)
The implementation of phytotechnologies to minimize the negative environmental impact of mining tailings requires the characterization of native plant species adapted and tolerant to soils contaminated with toxic metals. The objective was to identify and characterize native plant species with potential for phytoremediation of high Andean soils contaminated by mining tailings. The research was carried out in the tailings deposit area of the mining company "El Madrigal" in the district of Madrigal, Caylloma province, Arequipa, Peru; located at 15º35' S, 71º50' W and 3400 m altitude. Five sampling zones were established (first zone, and zones A, B, C and D). The concentration of contaminants in the soil samples with tailings was detected by inductively coupled plasma atomic emission spectrometry; the collection and identification of plant species was achieved by stratified systematic sampling, and the botanical samples were sent to the Michael Owen Dillon Scientific Institute for taxonomic identification according to the proposal of the Angiosperm Phylogeny Group. Similarity, diversity and equitability indices were used to characterize plant species. The most abundant plant species, and as such, with greater potential for phytoremediation were Cortaderia jubata, Baccharis sp, Stipa ichu and Juncus sp.; also, the species Eragrostis nigricans was included in this group because it was identified only in the first zone, the one with notable discharge of mining tailings. Consequently, these native species showed greater potential aptitude for phytoremediation of soils contaminated with As, Ba, Hg, Cd and Pb due to their adaptation and tolerance to adverse effects of contamination in high Andean soils.
Keywords: Mining tailings; phytotechnologies; soil remediation; tolerant plants